Persistence of silver nanoparticles in the rat lung: Influence of dose, size, and chemical composition. Issue 5 (August 2015) - Anderson, Donald S.; Silva, Rona M.; Lee, Danielle; Edwards, Patricia C.; Sharmah, Arjun; Guo, Ting; Pinkerton, Kent E.; Van Winkle, Laura S.
Abstract Increasing silver nanoparticle (AgNP) use in sprays, consumer products, and medical devices has raised concerns about potential health effects. While previous studies have investigated AgNPs, most were limited to a single particle size or surface coating. In this study, we investigated the effect of size, surface coating, and dose on the persistence of silver in the lung following exposure to AgNP. Adult male rats were intratracheally instilled with four different AgNPs: 20 or 110 nm in size and coated with either citrate or polyvinylpyrrolidone (PVP) at 0.5 or 1.0 mg/kg doses. Silver retention was assessed in the lung at 1, 7, and 21 d post exposure. ICP-MS quantification demonstrated that citrate-coated AgNPs persisted in the lung to 21 d with retention greater than 90%, while PVP-coated AgNP had less than 30% retention. Localization of silver in lung tissue at 1 d post exposure demonstrated decreased silver in proximal airways exposed to 110 nm particles compared with 20 nm AgNPs. In terminal bronchioles 1 d post exposure, silver was localized to surface epithelium but was more prominent in the basement membrane at 7 d. Silver positive macrophages in bronchoalveolar lavage fluid decreased more quickly after exposure to particles coated with PVP. We conclude that PVP-coated AgNPs had less retention in the lung tissue over time and larger particles were more rapidly cleared from large airways than smaller particles. The 20 nm citrate particles showed the greatest effect, increasing lung macrophages even 21 d after exposure, and resulted in the greatest silver retention in lung tissue.